Increase of Ship Power Plants Gas-Air Cooler Efficiency - Dymo B.V.; Voloshyn A.Y.; Yepifanov A.E.; Kuznetsov V.V. (Problems of the Regional Energetics)
Results of theoretical and experimental study of a gas-air cooler used to reduce the temperature of the exhaust gases of engines and boilers of ship power plants and the heat radiation of the chimney are presented in this paper. A Computational Fluid Dynamic (CFD) model of the gas-air cooler designed as an inhomogeneous ejector with a nozzle apparatus was developed. As a result of numerical simulation, the fields of temperature, pressure and velocity distributions along the gas-air cooler cross-sections were obtained. An experimental study of working model of the gas-air cooler at a scale of 1:5 was carried out. In the self-similarity region, characterized by Reynolds numbers (3.0-3.8)·105, the values of the resistance coefficient of the gas-air cooler model in the confidence interval ± 4.4 % fit on the line ςм = 2.52. A comparative analysis of the characteristics of gas-air flow, obtained during numerical simulation, with the results of thermal testing of working model of the gas-air cooler is given. The error in calculating of gas-air mixture temperature at the exit section of the gas-air cooler at 100 % load is 4.6 %. The CFD-modeling allows making calculations and optimization of new designs of the gas-air cooler at the design stage without carrying out thermal engineering tests both in the main and partial modes of operation.